Given the homogeneous differential equation in terms of a function y(t),
with initial conditions: , , , ,
Calculate
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This can be readily solved via a Laplace Transform given our boundary conditions at t = 0 . This computes to:
L ( y ( t ) ) = [ s 4 Y ( s ) − s 3 f ( 0 ) − s 2 f ′ ( 0 ) − s f ′ ′ ( 0 ) − f ′ ′ ′ ( 0 ) ] − Y ( s ) = 0 ;
or ( s 4 − 1 ) Y ( s ) − s 2 = 0 ;
or Y ( s ) = s 4 − 1 s 2 = ( s 2 + 1 ) ( s + 1 ) ( s − 1 ) s 2 = 2 ( s 2 + 1 ) 1 − 4 ( s + 1 ) 1 + 4 ( s − 1 ) 1 ;
or y ( t ) = L − 1 ( Y ( s ) ) = 2 1 sin ( t ) − 4 1 e − t + 4 1 e t .
At t = π we obtain:
y ( π ) = 2 1 sin ( π ) − 4 1 e − π + 4 1 e π = 2 1 sinh ( π ) ≈ 5 . 7 5 6
and ⌈ 5 . 7 5 6 ⌉ = 6 .